How to profit from the new global economy - Fitz-Gerald, Keith (Hoboken, N.J., 2010)
The rules of making money have changed-forever With the collapse of investment banks, trillion-dollar-plus government bailouts, and the Dow plunging like a rock, it's never been more important to understand-and actually profit from-the "new rules." Fact is, Fiscal Hangover, will give you an investing blueprint that will allow you to profit from the changing global economy.
Keywords: Tài chính quốc tế,Investments,International finance,Finance, Personal,Đầu tư,Tài chính cá nhân